Fine control of drug delivery for cochlear implant applications. (2nd October 2015) - Homsy, Alexandra; Laux, Edith; Brossard, Julien; Whitlow, Harry J.; Roccio, Marta; Hahnewald, Stefan; Senn, Pascal; Mistrík, Pavel; Hessler, Roland; Melchionna, Teresa; Frick, Claudia; Löwenheim, Hubert; et al.
Abstract : Cochlear implants are neuroprostheses that are inserted into the inner ear to directly electrically stimulate the auditory nerve, thus replacing lost cochlear receptors, the hair cells. The reduction of the gap between electrodes and nerve cells will contribute to technological solutions simultaneously increasing the frequency resolution, the sound quality and the amplification of the signal. Recent findings indicate that neurotrophins (NTs) such as brain derived neurotrophic factor (BDNF) stimulate the neurite outgrowth of auditory nerve cells by activating Trk receptors on the cellular surface (1–3 ). Furthermore, small-size TrkB receptor agonists such as di-hydroxyflavone (DHF) are now available, which activate the TrkB receptor with similar efficiency as BDNF, but are much more stable (4 ). Experimentally, such molecules are currently used to attract nerve cells towards, for example, the electrodes of cochlear implants. This paper analyses the scenarios of low dose aspects of controlled release of small-size Trk receptor agonists from the coated CI electrode array into the inner ear. The control must first ensure a sufficient dose for the onset of neurite growth. Secondly, a gradient in concentration needs to be maintained to allow directive growth of neurites through the perilymph-filled gap towards the electrodes of the implant. We used fluorescein as a test molecule for its molecular size similarity to DHF and investigated two different transport mechanisms of drug dispensing, which both have the potential to fulfil controlled low-throughput drug-deliverable requirements. The first is based on the release of aqueous fluorescein into water through well-defined 60-μm size holes arrays in a membrane by pure osmosis. The release was both simulated using the software COMSOL and observed experimentally. In the second approach, solid fluorescein crystals were encapsulated in a thin layer of parylene (PPX), hence creating random nanometer-sized pinholes. In this approach, the release occurred due to subsequent water diffusion through the pinholes, dissolution of the fluorescein and then release by out-diffusion. Surprisingly, the release rate of solid fluorescein through the nanoscopic scale holes was found to be in the same order of magnitude as for liquid fluorescein release through microscopic holes.